Numerical study on deformation behavior of bulk metallic glass composites via modified free-volume theory. (April 2020) - Zhao, J.X.; Chen, Y.F.; Wu, F.F.; Gong, J.M.
Abstract: A modified free-volume theory accounting for tensile and compressive strength asymmetry of bulk metallic glass (BMG) is implemented into finite element code as a user material subroutine. By means of representative volume element, systematical simulations are carried out to investigate the mechanical response as well as shear band evolution of BMG composites (BMGCs) under both tensile and compressive loadings. Comparison between experiments and simulations proves that this modified free volume model could yield acceptable prediction for both BMG matrix and BMGCs. Furthermore, free-volume is utilized to characterize the shear banding process of BMGCs, which is found to be dependent on volume fraction, shapes, orientation as well as yielding strength of particle materials. The present model could provide a computational tool to analyzing deformation behavior of BMGCs as well as designing new composites with high strength and plasticity. Highlights: Comparison between experiments and simulations on BMG matrix proves that this modified free volume model could yield acceptable precision which can account for hydrostatic stress contribution. Volume fraction of particle plays an important role in the global property of BMGCs. When the elastic modulus and yield strength of particle are lower than those in BMG matrix, higher volume fraction could result in a lower global strength of BMGCs, displaying a softening effect. However, it could enhance the ductility of the composite. Particle shape and orientation have limited effect on the stress-strain response of BMGCs; However, the yield strength of particle could largely affect the yield and ultimate strength of BMGCs.